American cutaneous leishmaniasis in infancy and childhood. (25th July 2017) - Paniz‐Mondolfi, Alberto E.; Talhari, Carolina; García Bustos, María F; Rosales, Tamara; Villamil‐Gomez, Wilmer E.; Marquez, Marilianna; Pérez Alvarez, Alexandra M.; Tálamo Sánchez, Alejandra I.; Rodriguez‐Morales, Alfonso J.
Abstract: Infant and young child skin diseases are among the most common features of morbidity throughout the tropics. Because the skin is directly exposed to the environment, it is considerably affected by climatic and local conditions such as vectors and microorganisms, as in the case of leishmaniasis. In America the observed magnitude of cutaneous leishmaniasis in children has led to the study of increased risk of exposure of this group due to the possibility of peri‐ and intradomiciliary transmission. The present review pretends to make a concrete approach all through the broad and main figures of this parasitic disease, including the clinical, physiopathological, epidemiological, diagnostic, and therapeutic aspects, in order to be used as a practical source of reference for pediatricians leading with tropical cutaneous pathology in the region.